Multiattribute evaluation - Edwards, Ward, 1927-2005.; Newman, J. Robert (John Robert), 1927- (Beverly Hills, [Calif.] ; London : SAGE, 1982)
This book presents one approach to evaluation, multiattribute utility technology, which stresses that evaluations should be comparative, and that all the different constituencies served by a programme and its different goals have to be kept in mind.
"A SAGE university paper."
Includes bibliographical references.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Evaluation research (Social action programs)